Hidden Curriculum: Investigating the Role of Student and Professor Voice in an Undergraduate ELT Context - Yekta Ghandi (Action Research Journal Indonesia (ARJI), 2025)
The hidden curriculum comprises unspoken or implicit values, behaviors, procedures, and norms in an educational setting. This can be an alternative to empowering attitudes, values, and non-cognitive skills in students. This study was an attempt to investigate the perceptions and views of ELT teachers and students about the hidden curriculum in the Iranian ELT context. To this end, a mixed method approach was used with the help of two instruments used in this study to investigate the proposed research questions. Therefore, two different populations, i.e., TEFL professors and TEFL students were selected. More specifically, a group of 20 TEFL professors were selected based on convenience sampling procedure. First of all, the SPSS data files was checked for missing data by taking frequency counts of the responses on all items from both data collection instruments. Secondly, the Cronbach alpha coefficients was computed in order to estimate the internal consistency reliability of each instrument. The findings of this study revealed that the ELT professors and students have positive perceptions and viewpoints towards the hidden curriculum in an undergraduate ELT context. And, there is significant difference between ELT professors and students’ viewpoints about hidden curriculum. This study has some theoretical and practical implications for policy makers, curriculum developers and instructors.